Irish roots [compact disc] - Hope, Daniel, 1974-; Armstrong, Siobhan; Garvey, Rea; Geiss, Daniel; Daly, Ross; Papanas, Simos; Forni, Emanuele E.; Forni, Emanuele E.; Chryssikos, Markellos; Galway, James; Galway, Jeanne; Groblewski, Ryszard, 1983-; et al. (Deutsche Grammophon, 2024)
Daniel Hope's latest album embodies his deep connection to Ireland, inherited from his paternal great-grandfather who left Waterford for South Africa in the 1890s. Although never residing in Ireland, Hope's fascination with its culture led to the creation of the documentary, Celtic Dreams: Daniel Hope's Hidden Irish History.